2023
DOI: 10.3389/fimmu.2023.1117255
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage repair-related lncRNAs signature predicts the prognosis and immunotherapy response in gastric cancer

Abstract: BackgroundGastric cancer (GC) is one of the most prevalent cancers, and it has unsatisfactory overall treatment outcomes. DNA damage repair (DDR) is a complicated process for signal transduction that causes cancer. lncRNAs can influence the formation and incidence of cancers by influencing DDR-related mRNAs/miRNAs. A DDR-related lncRNA prognostic model is urgently needed to improve treatment strategies.MethodsThe data of GC samples were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The dysfunction of the DDR process has been determined to have important implications for carcinogenesis, progression, treatment and prognosis in HCC. In previous studies, the DDR-related lncRNAs signature for prognostic prediction have been described in many kinds of cancers, such as gastric cancer [ 15 ], colon cancer [ 16 ], ovarian cancer [ 17 ], etc. However, the DDR-related lncRNAs in the HCC prognostic model remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunction of the DDR process has been determined to have important implications for carcinogenesis, progression, treatment and prognosis in HCC. In previous studies, the DDR-related lncRNAs signature for prognostic prediction have been described in many kinds of cancers, such as gastric cancer [ 15 ], colon cancer [ 16 ], ovarian cancer [ 17 ], etc. However, the DDR-related lncRNAs in the HCC prognostic model remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…STAD, a malignant tumour, is highly prevalent worldwide and has a poor prognosis ( 22 ). Research has demonstrated that lncRNA plays a regulatory role in the progression of gastric cancer, making it a promising target for the treatment of cancers ( 23 , 24 ). Lin et al identified lncRNA BC002811 as a promoter of gastric cancer metastasis through decoying SOX2 and inhibiting PTEN transcription ( 25 ).…”
Section: Discussionmentioning
confidence: 99%